Causes and Effects of Absenteeism among First Year College Students of the Mindanao State University – Sulu - Lukman, Adamel K. (Open Access Indonesia Journal of Social Sciences, 2021)
One of the major barriers to learning faced by the students and teachers in schools today is lack of consistent attendance. Poor student attendance has a far-reaching effect on the individual student especially on their academic performance in the school. This problem is caused by this major perennial problem—absenteeism. Absenteeism is a chronic absence in nature. It is habitual failure to attend school. When students regularly miss out classes consistently would entail disadvantages academically. However, the main purpose of this study was to identify the causes and effects of absenteeism among first year college students of the Mindanao State University-Sulu, as well as to determine and figure out possible remedies to address this problem. In analyzing and computing the data, the researcher used SPSS version 21.0, and utilized checklist questionnaire and an open-ended questionnaire, respondents were consisted of 100 first year college students and 9 faculty members the researcher was able to find out the leading cause of absenteeism among the first year college students of MSU-Sulu and that is ‘school is far from home’ with (3.06) mean value . While low grade point average (GPA) with mean value (3.78) was the leading effect of absenteeism followed by poor critical thinking skills, other effects of absenteeism were, poor classroom performance, low examination results, poor oral recitation, poor creative skills, poor communication skills, lack of self-confidence, low comprehension and high risk of dropouts. The researcher was able to figure out remedies that can be applied to address the problem on absenteeism. The remedies include (a) there must be a student dormitory inside the campus to house the students since majority of the students enrolled in the university are from distant island municipalities (b) conduct orientation to students and parents prior to the opening of regular classes (c) the university must have a strict policy dealing with students’ absenteeism (d) teacher or instructor should conduct regular assessment in the form of quiz at the end of the session (e) motivate and encourage the students to give more attention and emphasize the importance of education in their future (f) classroom atmosphere should be conducive to learning.